THINKING TACTIC OF PROFESSIONAL LANGUAGE TERMINOLOGY ACQUISITION - Dieorditsa, Taiana; Voronina, Maryna; Yepifanova, Olga; Tolmachov, Volodimir (Physical and Mathematical Education, 2022)
Formulation of the problem. The basis of the proposed development is the results of the logical analysis of language as a sign system as well as the results of analysis operations with concepts as a system of thinking procedures. According to our observations, there are many students who face difficulties in understanding the research definitions. As it is impossible to teach understanding, we wondered about what thinking tactics provide conscious learning of terms? Materials and methods. The basis of the proposed development is the result of the logical analysis of language as a sign system. The idea of performing over the notion of analytical and synthetic logical operations based on both types of hierarchical relations between notions — "genus/species" and "whole/part", arises from the general morphological analysis of F. ZwickyResults. It has been found that the term as a linguistic sign has three main attributes: meaning of the object, sense, and semantic content. The sense of the term is fixed by the definition, and the semantic content is attributed to it by the characteristic — cognitive technique like the definition. Semantic content, in contrast to the sense of the term, is a set of unstructured information. The thinking tactics in question are aimed at developing the subject's ability to learn to understand the sense of a term by giving a structural organization to its semantic content. It is proposed to structure the semantic content of the term by solving two specific tasks. Inference of terms — keywords of the structure sought — is the essence of the first task. Reproduction of the structure of the semantic content of the learned term constitutes the second task. The mental tactics are the embodiment of the pedagogical technique described in the logical theory of the concept: cognitive techniques that are like the definition must precede it because their application often facilitates the understanding and assimilation of the definition of the term.Conclusion. The proposed mental tactics of learning the term will be effective if the subject of learning: 1) is able to establish and define hierarchical connections between concepts; 2) knows the nature, structure, and rules of execution of the concept of logical operations: generalization, taxonomic and mereological divisions, mereological integration; 3) has regulatory procedures that are the components of these operations; 4) has the means to control the correctness, compliance operations, and derived terms.
Keywords: understanding; sense of a term; semantic content of a term; structuring; a notion; operating with a notion